ANALYTICAL CHEMISTRY ZOL-GEL IS PRODUCED ON THE BASIS OF PROCESSES AMMONIA USES NANOMATERIALS CREATION OF SELECTIVE GAS SENSORS - Abdurakhmanov Ergash; Ilkhom Er. Abdurakhmanov; Begimkulov Jorakul Nurillaevich; Ismoilov Eldor Khalilovich; Farrukh F. Kholmurzaev (European Science Publishing, 2023)
Today, the use of selective methods and sensitive sensors is rapidly developing in industry, in solving environmental problems, especially in solving the problem of atmospheric air monitoring, which has arisen worldwide as a result of the rapid development of chemistry, oil and gas. chemistry. Semiconductor sensors (SPDs) are sensitive devices, and their main advantages are ease of use, small size, long working life, high accuracy and speed. Semiconductor gas sensors based on nanomaterials obtained using sol-gel processes, sol-gel technology for the manufacture of ammonia semiconductor sensors, and studies of the hydrolytic polycondensation of TEOS during the synthesis of gas-sensitive nanocomposite films have been studied.
Keywords: semiconductor sensor, catalyst, selectivity, sensing elements, iron oxide, titanium oxide, ammonia, tetraethoxylane.